THE PRACTICE OF PHYSICAL ACTIVITIES IN THE FIGHT AGAINST CHILDHOOD OBESITY (Fiep Bulletin - online, 2025)
Introduction: Childhood obesity is an urgent global issue that requires effective and comprehensive interventions. Objective: The aim of this study was to investigate the importance of regular physical activity in the fight against childhood obesity. Methods: To this end, a systematic review of the literature was carried out, conducted through searches of academic articles on the SciELO and Google Scholar platforms. The keywords "childhood obesity", "physical activity", "prevention" and "treatment" were used. As inclusion criteria, articles published in the last 20 years, relevant to the study of childhood obesity and physical activity, and being available in Portuguese or English, were accepted. Articles that did not meet these criteria were excluded from the analysis. Results: Three studies were selected to compose the sample of this research. The results of the reviewed articles highlighted that physical activity not only helps reduce body weight, but also improves metabolic health, being most effective when combined with nutrition education and the active participation of families and communities. Conclusion: It was concluded that the integration of physical activity with educational initiatives and supportive public policies is vital to address childhood obesity.
Keywords: Childhood Obesity; Physical Activity; Prevention; Treatment